Longitudinal follow-up of rehabilitations on mandibular implants: analysis of patient satisfaction rates and behavior of dentures and components - Ana Flávia Sanches Borges; Ana Cláudia Moreira Melo; Ivete Aparecida de Mattias Sartori; Geninho Thomé; Jacira Nara Acunha (Faculdade São Leopoldo Mandic, 2009)
Objectives: Analyze the behavior of implants and demtures of cases treated at the dental implant improvement center of the Instituto de Ensino, Aperfeiçoamento e Pesquisa em Odontologia do Mercosul school, Porto Alegre, RS, Brazil, and to evaluate the importance of long-term follow-up. Methods: Twenty nine patients with a mean age of 64 years, and 120 implants (Neodent Implantes Osseointegráveis, Curitiba, Brasil) were evaluated. The rehabilitations were mandibular complete fixed dentures. The evaluation item used in the Kaplan-Meier survival statistic analysis was the number of implants in function with no mobility (success) and the number of prosthetic screws that remained tight after periods ranging from 18 to 72 months of the prostheses in mouth. Results: The survival analysis revealed that 100% of 120 implants were successful and 85% of the screws remained tightly fastened. The results showed that the implants were successful irrespective of the period in function and irrespective of whether or not the dentures received immediate load; however, the screws did not show the same success rate, since loosening occurred in the course of time. The patient rate of satisfaction with the treatment was 82,75%. Conclusion: Based on the data it was concluded that long-term follow-up is a very important clinical procedure for maintaining the success achieved.